2021
DOI: 10.3389/fchem.2021.650880
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Potential Equation for Modeling Triboelectrochemical Reactions on Solid–Liquid Interfaces

Abstract: Triboelectrochemical reactions occur on solid–liquid interfaces in wide range of applications when an electric field strong enough and a frictional stress high enough are simultaneously imposed on the interfaces. A characteristic of triboelectrochemical reactions is that not only the thermal energy but also the electrical and mechanical energies can activate, assist, or mitigate the solid–liquid interface chemical reactions, the products of which affect electrical and tribological behavior of the interfaces in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Liu et al [119] designed a three-electrode friction system and verified the feasibility of theory. The important discovery is that the lubricated friction can be controlled by the applied elasticity.…”
Section: Electricity-assisted Mechanical Processingmentioning
confidence: 97%
See 1 more Smart Citation
“…Liu et al [119] designed a three-electrode friction system and verified the feasibility of theory. The important discovery is that the lubricated friction can be controlled by the applied elasticity.…”
Section: Electricity-assisted Mechanical Processingmentioning
confidence: 97%
“…Gutman [117] and Chen [118] suggested that concept of chemical potential, instead of Gibbs free energy, should be used in material science. Based on this concept, Liu et al [119] proposed their model for explaining the process of tribo-electrochemistry, which can be used to analyze the electricity-assisted manufacturing process.…”
Section: Electricity-assisted Mechanical Processingmentioning
confidence: 99%
“…As we know, the traditional electrochemical processes generally include adsorption/desorption processes when the surface potential of electrode is within the electrochemical potential window, reduction process at negative and oxidation process at positive potentials. For the electrode processes with the influence of external forces, triboelectrochemical processes including frictioninduced reduction, friction-inhibited reduction, friction-induced oxidation, and friction-inhibited oxidation should be involved [22]. Friction could affect the electrode processes, as well as the electrochemical potential window.…”
Section: Electrode Processes and Electrochemical Potential Windowmentioning
confidence: 99%
“…The types and structures of the oxides affect the tribological behaviors mostly. For example, CuO or CuO 2 can reduce the friction coefficient [22,29]. While, iron oxides increase the friction coefficient [7].…”
Section: Wear Map Under Different Surface Potentialsmentioning
confidence: 99%
See 1 more Smart Citation